2021
DOI: 10.1111/famp.12659
|View full text |Cite
|
Sign up to set email alerts
|

Implementing Behavioral Couples Therapy for Substance Use Disorders in Real‐World Clinical Practice

Abstract: Behavioral couple therapy (BCT) is an evidence‐based, manualized treatment that has been primarily developed to treat alcohol use disorder. The treatment model leverages the intimate partner relationship to support recovery. Although the efficacy of BCT is well‐supported in randomized controlled trials, little attention has been given to the translation of BCT to everyday practice settings. This article presents recommendations for implementing BCT in such settings. We describe a stepwise approach for getting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 45 publications
0
3
0
2
Order By: Relevance
“…Effectiveness studies of substance use interventions in real‐world settings are lacking (McCrady et al, 2016; Schumm & Renno, 2022). Conducted in two publicly funded addiction outpatient clinics, this clinical trial offers also pragmatic evidence (Ford & Norrie, 2016), thereby increasing the feasibility of applying CCT in real‐world clinical practice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Effectiveness studies of substance use interventions in real‐world settings are lacking (McCrady et al, 2016; Schumm & Renno, 2022). Conducted in two publicly funded addiction outpatient clinics, this clinical trial offers also pragmatic evidence (Ford & Norrie, 2016), thereby increasing the feasibility of applying CCT in real‐world clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…Both models were found to be “probably efficacious” as stand‐alone treatments for drinking outcomes (Hogue et al, 2022, p. 178). Real‐world effectiveness studies for these models are currently limited (McCrady et al, 2016; Schumm & Renno, 2022). A recent meta‐analysis drew more cautious conclusions in relation to BCT outcomes for substance use and relationship adjustment in comparison with alternative treatment methods, including individual‐based treatments and brief couples' therapy (Schmit et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Hierdurch wird der Befähigung stattgegeben, in der medizinischen Rehabilitation Abhängigkeitserkrankter eigenverantwortlich Einzel-und Gruppentherapiesitzungen durchzuführen. Weiterbildungen zu Suchttherapeut:innen auf Grundlage der Systemischen Therapie können von der DRV "grundsätzlich akzeptiert" werden -so der Wortlaut einer Mitteilung der zuständigen Abteilung der DRV an Weiterbildungsinstitute mit ‚anerkannten Curricula' [49]. Durch diese Aussicht könnten systemisch-familientherapeutische Weiterbildungen im Rahmen der Suchtrehabilitation etabliert werden, um sie folglich als von der DRV anerkannte Suchttherapieform anbieten zu können.…”
Section: Ein Exemplarischer Ausschnitt Gegenwärtiger Versorgungsstruk...unclassified
“…Auch in den USA werden SGS mittlerweile im Kontext und in der Wechselwirkung mit dem sozialen Umfeld und der Familie betrachtet, wodurch es nur begrenzt wirksam erscheint, lediglich die Betroffenen mit der aktiven SGS zu behandeln [50]. Schon länger existieren international einige gute Ansätze [51,52], die bereits in mehreren Rehabilitationseinrichtungen in den Vereinigten Staaten flächendeckend Anwendung finden [53]. In Deutschland sind diese nach wie vor nicht bedarfsgerecht in Institutionen der Suchthilfe implementiert, können jedoch auch auf nationaler Ebene als vielversprechende Orientierung für die Praxis dienen.…”
Section: Ein Exemplarischer Ausschnitt Gegenwärtiger Versorgungsstruk...unclassified
“…Evidence for the causal effects of homework ( d = 0.53; 95% confidence interval [CI] = 0.35–0.72, p < 0.0001 in Kazantzis, Whittington & Dattilio, 2010) and for homework adherence as a predictor of symptom reduction (correlational effects, r = 0.26; 95% CI = 0.19–0.33 in Mausbach, Moore, Roesch, Cardenas & Patterson, 2010) is compelling, but perfect adherence is not expected because CBT supports change through a process of experimentation (i.e., collaborative empiricism, see discussion in Dozois, 2010). Prior surveys have confirmed that rates of homework adherence are often less than 100% in clinical practice (Helbig & Fehm, 2004; Kazantzis, Lampropoulos & Deane, 2005), and guidance has been provided for maximizing homework adherence in couples and family therapy work (Bevilacqua & Dattilio, 2001; Dattilio, 2002, 2005; Dattilio & Dickson, 2007; Dattilio, L'Abate & Deane, 2005; Epstein & Baucom, 2007; Newcomb & Lebow, 2007; Robbins, Szapocznik & Perez, 2007; Schumm & Renno, 2022). However, little research has surveyed couples and family therapists' experiences of CBT, and no prior study has examined the potential for positive or negative impact of homework non‐completion (IHN) on the working alliance (see reviews in Mutschler, Malivoire, Schumm & Monson, 2022; Sibley, Link, Torres Antunez & Greenwood, 2022).…”
Section: Introductionmentioning
confidence: 99%